Advances in Clinical Audiology 2017
DOI: 10.5772/66206
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Evoked Brainstem Response

Abstract: The auditory brainstem response (ABR) is a clinical tool to assess the neural functionality of the auditory brainstem. The use of verbal stimuli in ABR protocols has provided important information of how the speech stimuli are processed by the brainstem structure. The perception of speech sounds seems to begin in the brainstem, which has an important role in the reading process and the phonological acquisition speech ABR assessment allows the identification of fine-grained auditory processing deficits, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Synchronization is important for adequate learning development and is a fundamental operating principle of brainstem function, specifically in spectral and temporal coding. The FFR has been shown to be an electrophysiological instrument capable of monitoring the neural development of speech sounds in a fast, reliable, and objective manner, and has often been recommended as a way of detecting an infant's ability to acquire language, speech, and learning at an early stage [36][37][38][39]. In a recent study, researchers have demonstrated that infants with congenital toxoplasmosis have disorganized neural coding of speech.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronization is important for adequate learning development and is a fundamental operating principle of brainstem function, specifically in spectral and temporal coding. The FFR has been shown to be an electrophysiological instrument capable of monitoring the neural development of speech sounds in a fast, reliable, and objective manner, and has often been recommended as a way of detecting an infant's ability to acquire language, speech, and learning at an early stage [36][37][38][39]. In a recent study, researchers have demonstrated that infants with congenital toxoplasmosis have disorganized neural coding of speech.…”
Section: Discussionmentioning
confidence: 99%
“…They emphasize that hearing disorders need to be treated in an interdisciplinary context, one which should include, depending on the case, the following professionals: speech therapist, psychologist, audiologist, and neurologist [3]. In this way, electrophysiological assessments can play an important role both in the process of assessing auditory processing and also in monitoring auditory rehabilitation programs, such as auditory training [30].…”
Section: Hearing Electrophysiologymentioning
confidence: 99%